Karakteristik Histopatologi dan Stadium Klinis Kanker Nasofaring - Asep Kuswandi; Nisa Habibah Kuswandi; Muslim Kasim; Tan’im Tan’im; Mardheni Wulandari (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Nasopharyngeal Cancer is an endemic disease in Southeast Asian and China. The incidence of nasopharyngeal cancer will raise at 30 years old and will reach its peak in 46 – 55 years old. The incidence of nasopharyngeal cancer is 2 – 3 fold higher in man. Nasopharyngeal cancer patients are usually diagnosed at a late stage so they have a bad prognosis. Based on the problem above the author want to study the Characteristic of Histopathology and Clinical Stage of Nasopharyngeal Cancer in RSUD Dr. H. Abdul Moeloek Period 2016 – 2019. Aims: This study wants to know about the Characteristic of Histopathology and Clinical Stage of Nasopharyngeal Cancer, the frequency distribution of Nasopharyngeal Cancer based on gender and age in RSUD Dr. H. Abdul Moeloek Tahu 2016-2019. Methods: This study used a retrospective descriptive study with 63 patients in RSUD Dr. H. Abdul Moeloek Period 2016 – 2019.Result: Based on the obtained data, the number of nasopharyngeal cancer cases in RSUD Dr. H. Abdul Moeloek Period 2016 – 2019 increased annually. The total samples that were used in this study were 63 samples. The highest distribution of nasopharyngeal cancer which is sorted by age is the group of 46 – 55 years old with 28.6%. The highest distribution of nasopharyngeal cancer which is sorted by sex is the man with 65%. The highest distribution of nasopharyngeal cancer which is sorted by Histopathology classification is Nonkeratinizing Cell Carcinoma – Undifferentiated subtype with 71.4%. The highest distribution of nasopharyngeal cancer which is sorted by the clinical stage is Stage III with 63.3%. Conclusion: This study reveals the Characteristic of Histopathology and Clinical Stage of Nasopharyngeal Cancer, the frequency distribution of Nasopharyngeal Cancer based on gender and age in RSUD Dr. H. Abdul Moeloek Tahu 2016-2019.